Predictive markers of radiotherapy-induced rectal cancer regression. Issue 10 (12th August 2014) - Shin, J-S; Tut, T-G; Ho, V; Lee, C S
Abstract : Patients with locally advanced rectal cancer receive preoperative radiotherapy to reduce the probability of recurrence and to possibly improve overall survival. However, this appears dependent on the extent of histological tumour regression seen in the resected bowel, which can be highly variable between individuals. No predictive marker that can stratify patient management in this regard is currently available. Experimental data implicates a variety of factors that are involved in the DNA damage response following radiation injury, tumour tissue oxygenation, autoimmune antitumour response triggered by radiotherapy and in the pathogenesis of colorectal cancer, as potential indicators of radiation sensitivity. These details are presented in this review, which may serve as targets for clinical validation studies aiming to find predictors of radiotherapy response in rectal cancer.